Training Digital Competencies in Future Primary School Teachers: A Systematic Review - Marina Alférez-Pastor; Rocío Collado-Soler; Virginia Lérida-Ayala; Ana Manzano-León; José Manuel Aguilar-Parra; Rubén Trigueros (MDPI AG, 2023)
Technology proliferated in our daily lives, including in the educational system. To make good use of it, it is so important that teachers have the best training in its use and possibilities. The main objective of this study was to analyze the different methods of training for future primary school teachers and assess the efficacy of the methods. We used SCOPUS, and Web of Science databases to carry out this systematic review and we followed the PRISMA statement. Two authors independently conducted the literature search, and then, they reached a consensus. A total of 13 relevant articles were selected to be analyzed in detail. Our results showed that the training programs carried out improved the digital competencies of students of primary education degrees. Moreover, they improved the knowledge of theoretical content, improved linguistic competence and fostered cooperative work and creativity. In conclusion, we encourage teachers, not only future teachers but also current teachers, to take these types of training programs in order to improve their digital competency, which is a necessity in current society.